Making a Turtle Conservation Website and Sumbreng Sea Pearl Education Tour for Ecosystem Balance - Anggara Trisna Nugraha; utomo, Devina Puspita Sari; utomo, Diego Ilham Yoga Agna; utomo, Salsabila Ika Yuniza; Riyadi, Faris; Rahmat Adzani, Fajar; utomo, Andika Aldo Pratama; utomo, Rahmania Firdiansyah (Frontiers in Community Service and Empowerment, 2023)
The coast is an area that has the potential to be used as a tourist spot, including for turtle conservation which is relied on as an economic support. Turtles are one of the animals protected by law. Not only are they protected by law because it is feared that they will eventually become extinct, but in marine ecosystems turtles also have their own benefits. The Turtle Conservation "Mutiara Laut Masaran" which is located on Sumbreng Beach, East Java is one of the turtle conservation areas developed by the Lentera Trenggalek Community. Activities carried out at the "Mutiara Laut Masaran" turtle conservation include relocating turtle eggs, rearing turtle eggs, combing eggs, and also releasing hatchlings. There are 5 types of turtles that are protected on Sumbreng beach, some of which are green turtles and hawksbill turtles, which are included in the Appendix I category, which means they are prohibited from international trade. Apart from visiting tourists being able to see the turtle breeding process, this conservation also provides economic tourism such as small Jeep facilities that are used to get around the beach and the release of hatchlings in certain months. However, due to the lack of exposure to this conservation area. This results in a small number of tourists coming, and also some tourists who come in the wrong months and cannot directly see the hatchlings being released onto the beach. Therefore, this dedication brings an innovation in the form of a website facility which is useful for updating all activities taking place at the "Mutiara Laut Masaran" Turtle Conservation. So it can attract more tourists to visit this tourist attraction and tourists can also find out which months are effective for visiting this tourist attraction. It is hoped that the "Mutiara Laut Masaran" turtle conservation can have the potential for educational tourism which can be developed further, so that it can support the economy of the surrounding community and can also be used as a source of income to manage the turtle conservation itself.